2001
DOI: 10.1002/bit.1068
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the maximum specific uptake capacities for glucose and oxygen in glucose‐limited fed‐batch cultivations of Escherichia coli

Abstract: A simple pulse-based method for the determination of the maximum uptake capacities for glucose and oxygen in glucose limited cultivations of E. coli is presented. The method does not depend on the time-consuming analysis of glucose or acetate, and therefore can be used to control the feed rate in glucose limited cultivations, such as fed-batch processes. The application of this method in fed-batch processes of E. coli showed that the uptake capacity for neither glucose nor oxygen is a constant parameter, as of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
88
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 33 publications
6
88
0
Order By: Relevance
“…The average cellular respiration rate is calculated by normalizing OUR to population size. Most studies of this nature determine respiration rates while cells are growing (9)(10)(11)(12)(13)(14). In the rare cases where respiration was measured after cells exited exponential-phase growth (15,16), respiration rates dropped significantly-presumably as the cells became increasingly nutrient limited.…”
mentioning
confidence: 99%
“…The average cellular respiration rate is calculated by normalizing OUR to population size. Most studies of this nature determine respiration rates while cells are growing (9)(10)(11)(12)(13)(14). In the rare cases where respiration was measured after cells exited exponential-phase growth (15,16), respiration rates dropped significantly-presumably as the cells became increasingly nutrient limited.…”
mentioning
confidence: 99%
“…In the literature, several specific fermentation strategies are mentioned to reduce acetate production [1,[16][17][18][19][20]. levels were developed.…”
mentioning
confidence: 99%
“…Many data in literature showed that E. coli grows in salt-based chemically defined media [19,39] as long as an organic carbon source is provided [22], as well as in rich complex organic media. Nevertheless, higher complexities in medium composition can lead to a lower reproducibility of the cell metabolic response and, therefore, lower the possibility of a well-controlled process [31].…”
mentioning
confidence: 99%
“…However, much work has to be done in order to establish the instant and profile addition of the growth-limiting carbon, often glucose [19,32] or glycerol [38].…”
mentioning
confidence: 99%